ANALISIS PENGARUH RETURN ON ASSETS, CURRENT RATIO, DEBT TO ASSETS RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Marito Siregar, Elandhra; Hasianda Tigor, Ryan; Oktalina, Gayatria (Jurnal Progresif Manajemen Bisnis, 2024)
Analysis of The Effect of Return on Assets (ROA), Current Ratio (CR), Debt to Assets Ratio (DAR) on Stock Prices ( in Telecommunications Companies Listed on the Indonesia Stock Exchange 2018- 2022). This study aims to analyze the effect of Return on Assets (ROA), Current Ratio (CR), Debt to Assets Ratio (DAR) on Share Price of Telecommunications Companies Listed on the Indonesia Stock Exchange in 2018-2022 either partially or simultaneously. The number of samples used in this study were 4 Telecommunications companies listed on the Indonesia Stock Exchange from a total population of 17 companies. The type of data is secondary data sourced from the company's financial statements and annual reports. The data analysis method used is multiple linear regression analysis. The results of hypothesis testing in this study indicate that simultaneously Return on Assets (ROA), Current Ratio (CR), Debt to Assets Ratio (DAR) have significant effect on stock prices. Partially, Return on Eq (ROA) have no effect on stock prices. Meanwhile, Current Ratio (CR), Debt to Assets Ratio (DAR) has an effect on stock prices